Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja Karyawan Kantor Besar Pada PT. Ivo Mas Tunggal SSMM Di Kecamatan Kandis - Hendrayani, Hendrayani (Eko dan Bisnis: Riau Economic and Business Review, 2023)
The research was conducted at PT. Ivo Mas Tunggal. Based on the background of the research stated above, Data analysis in this study was carried out using method descriptive Â  and quantitative . Method descriptive that is data analysis with way decomposition theories contained in list library and connected with data obtained from results research that will collected, grouped and tabulated then taken conclusion . And method quantitative with technique multiple linear regression . Samples taken in research this is amounting to 98 people ( respondents ), the results of the research were obtained obtained results from uji_F from table above to show Sig value. As much as 0,000 more small from 0.05%. Or value F_count as big as 21,847 Meanwhile value F table could obtained namely N1 = k-1 (7-1 = 6) and N2 = nk (60-7 = 53) then obtained value F table Â  at N1 = 6 and N2 = 53 so obtained value F table amounting to 2.28 then could concluded that in a manner together (wage adequate, fair treatment, tranquility work , feeling recognized , award on results work , distributor feeling ) has a significant effect to Satisfaction Work society at PT. Ivo Mas Tunggal SSMM in Kandis Subdistrict , and value Adjusted R_ Square of 0679 means magnitude influence / contribution or contributions made variable free that is adequate wages, fair treatment, tranquility work , feeling recognized , award on results work , distributor feeling to satisfaction consumer as big as 67.9 percent while the rest amounted to 32.1 percent influenced by other factors that don't enter in research.